DIGITAL LEARNING INNOVATION AS A STRATEGY TO IMPROVE THE QUALITY OF ISLAMIC EDUCATION IN MADRASAH - Hutasuhut, Sartika; Azzahra, Fatimah; Faradila, Futri; Basit, Abdullah; Hasibuan, Rahma Isna Hayati; Awaluddin (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2025)
This study investigates digital learning innovation as a strategy to enhance the quality of Islamic education in madrasahs. Employing a literature review method, the research synthesizes findings from scholarly books, journals, and educational articles related to digital-based learning. Results show that digital learning supports more interactive and flexible learning processes, increases student engagement, enhances independent learning, and improves teacher effectiveness in delivering material and monitoring student progress. However, the effectiveness of these innovations depends on the digital readiness of educators, learners, and infrastructure. Therefore, teacher training, adequate facilities, and stakeholder collaboration are essential to successful implementation. This study serves as a reference for the development of Islamic education that is responsive to technological advancements. Penelitian ini mengkaji inovasi pembelajaran digital sebagai strategi untuk meningkatkan mutu pendidikan Islam di madrasah. Dengan menggunakan metode studi pustaka, kajian ini mengolah temuan dari buku, jurnal, dan artikel ilmiah yang relevan mengenai pembelajaran berbasis digital. Hasil penelitian menunjukkan bahwa pembelajaran digital mendukung proses belajar yang lebih interaktif dan fleksibel, meningkatkan keterlibatan siswa, memperkuat kemandirian belajar, serta meningkatkan efektivitas guru dalam menyampaikan materi dan memantau perkembangan peserta didik. Namun, efektivitas inovasi ini bergantung pada kesiapan digital pendidik, peserta didik, serta sarana pendukung. Oleh karena itu, pelatihan guru, penyediaan infrastruktur yang memadai, dan kolaborasi dengan pemangku kepentingan menjadi faktor kunci keberhasilan. Penelitian ini diharapkan menjadi rujukan dalam pengembangan pendidikan Islam yang adaptif terhadap kemajuan teknologi.